2021
DOI: 10.1519/jsc.0000000000003817
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training, Fatigue, Quality of Life, Anxiety in Breast Cancer Survivors

Abstract: Moraes, RF, Ferreira-Júnior, JB, Marques, VA, Vieira, A, Lira, CAB, Campos, MH, Freitas-Junior, R, Rahal, RMS, Gentil, P, and Vieira, CA. Resistance training, fatigue, quality of life, anxiety in breast cancer survivors. J Strength Cond Res 35(5): 1350–1356, 2021—Resistance training (RT) has shown to be effective in improving fatigue, quality of life (QOL), and anxiety levels among breast cancer survivors (BCS), but there is no consensus as to how this practice should be prescribed for optimal performance. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Moreover, after 9 months of MCT protocol was effective in improving the global health and QoL of women who survived BC in 57% change from baseline, with a moderate ES, η 2 = 0.320 for the aspect of the AD functionality, 50% from baseline, with a moderate ES, η 2 = 0.280, in emotional aspects, 33% change from baseline, with a small ES, η 2 = 0.141 in the perception of pain, -66.8% change from baseline with a large ES, η 2 = 0.317 in the perception of fatigue, with -75% change from baseline, with a moderate ES, η 2 = 0.380 in the perception of global health and QoL. In a similar way to our findings, studies analyzing the effects of resistance training [62] , and aerobic training [63] , have verified significant improvements in the QoL of women survivors of BC [45,63] . The increase in QoL after BC treatment is an important factor in preserving women's mental health, self-esteem, and confidence in their survival, and in moving forward in life, thus maintaining their skills and abilities, so that they can be productive in society to which they belong, therefore it may also contribute to better social relationships in daily life for this women [64] .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, after 9 months of MCT protocol was effective in improving the global health and QoL of women who survived BC in 57% change from baseline, with a moderate ES, η 2 = 0.320 for the aspect of the AD functionality, 50% from baseline, with a moderate ES, η 2 = 0.280, in emotional aspects, 33% change from baseline, with a small ES, η 2 = 0.141 in the perception of pain, -66.8% change from baseline with a large ES, η 2 = 0.317 in the perception of fatigue, with -75% change from baseline, with a moderate ES, η 2 = 0.380 in the perception of global health and QoL. In a similar way to our findings, studies analyzing the effects of resistance training [62] , and aerobic training [63] , have verified significant improvements in the QoL of women survivors of BC [45,63] . The increase in QoL after BC treatment is an important factor in preserving women's mental health, self-esteem, and confidence in their survival, and in moving forward in life, thus maintaining their skills and abilities, so that they can be productive in society to which they belong, therefore it may also contribute to better social relationships in daily life for this women [64] .…”
Section: Discussionsupporting
confidence: 87%
“…For instance, this would be the case of breast cancer survivors who suffer an important degree of fatigue due to the treatments they receive. Several studies have reported significant gains with protocols of three sets with 8–12 RM and 2 min of rest [ 29 ]. As has been documented, these protocols are not only difficult to reproduce rigorously, showing no better results in the improvement of strength [ 30 , 31 ], but they also involve an important fatigue, which should be controlled through a greater control of the applied stimulus and recoveries much better adjusted to the possibilities or individual needs of each subject.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 325 participants (96 males and 229 females) were included in this review. Participant cohorts included female-only BCS [52][53][54]56,58], ECS [51], and PCS [55,57]. Sample sizes ranged from 14 to 66, while age ranged from 35 to 77 years old.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The countries or region of publication were as follows; Australia (n = 1), Brazil (n = 1), Canada (n = 2), India (n = 1), Iran (n = 1), and the United States of America (n = 2). Hagstrom et al [52], Moraes et al [54], Norris et al [55] and Santa Mina et al [57] included participants on adjuvant therapies.…”
Section: Participant Characteristicsmentioning
confidence: 99%